War, Immigration, Oral Collision, and the Transmission of Values: Studying the content analysis of two novels “The Fall of the Heavens and the Period of Belkis Crying” in the light of George Lukacs’ theory - Izaddin Abdulsamad Rasool; Khdir Rasul Ababakr (QALAAI ZANIST JOURNAL, 2022)
War and immigration are two social and political phenomena since antiquity. They have existed throughout human history and still exist to this day, and the relationship between the two phenomena is always clear. And the history of Kurdish society was also not without the phenomenon of war and migration, which led to deprivation and social deterioration. The events that resulted in war and migration are clearly recorded in the literature in general and the core of the novels in particular, that is, the prevailing reality, and they became a manifestation and reflection of the events in the Kurdish novel. Therefore, this study is in the context of literary sociology based on the updated theorist (George Lukacs) in explaining and analyzing the phenomena that resulted from the war. For this purpose, the two novels The Fall of the Heavens and The Age of Belqis Crying were highlighted as examples of the research and studies that were taken, based on the methodology of content analysis and referring to the phenomenon of war, migration, verbal collision and the transfer of values ​​as a result of war and migration.